Examining the association between future pregnancy intentions, contraceptive use and repeat pregnancies among women living with HIV in Cape Town, South Africa - Mubangizi, Lilian (Department of Public Health and Family Medicine, 2021)
Background: Given the rapid expansion of antiretroviral therapy (ART) services in South Africa, there is growing recognition of the importance of fertility intentions, contraceptive use and childbearing among women living with HIV (WLHIV). With the integration of family planning services in the prevention of mother-to-child transmission of HIV (PMTCT) services, understanding fertility intentions and contraceptive use is crucial in evaluating such programs. We investigated the relationship between future fertility intentions, contraceptive use and repeat pregnancies among WLHIV in Cape Town, South Africa. Methodology: We analyzed data from the MCH-ART study conducted at the Gugulethu Midwife Obstetric Unit (MOU) in Cape Town, South Africa, which followed women initiating ART during pregnancy through 36-60 months postpartum. Self-report data were collected using standardized questionnaires at repeated study visits. Data on repeat pregnancies were abstracted from the Western Cape Provincial Data Centre. Associations between maternal characteristics and repeat pregnancies were examined using Cox proportional hazards models. Results: Overall, 109 incident repeat pregnancies were recorded among the 471 women included in this analysis. The median time at risk per individual was 4.27 years. The rate of repeat pregnancies was 5.72 per 100 person-years (PY). This rate was significantly lower among women aged 35-45 years (2.11/100PY) compared to women aged 18-24 years [7.56/100 PY; adjusted hazard ratio (aHR), 0.26: 95% confidence interval [CI], 0.09, 0.81). A total of 333 women contributed data on future fertility intentions and contraceptive use at 12 months postpartum, with 9% reporting that they wanted another child in the future, and 82% reporting current contraceptive use; 16% (n=54) reported not wanting another child but no contraceptive use. The rate of repeat pregnancies was 3 folds higher among women who reported wanting a child in the future (12.59/100 PY) compared to women who did not want 5 a child in the future (4.31/100 PY; aHR, 3.46: 95% CI, 1.83, 6.50). Contraceptive use at 12 months postpartum was not associated with repeat pregnancies. Women who did not want a child and used contraceptives had a 45% decreased hazard of repeat pregnancies compared to women who did not want a child and did not use contraceptives (aHR 0.55: 95% CI [0.32, 0.94]. Conclusion: Among women initiating ART during pregnancy, a repeat pregnancy incidence rate of 5.72/100 PY was observed through 36-60 months postpartum, with the incidence lower among older women. At 12 months postpartum, a notable proportion of women reported not wanting another child but no contraceptive use. Wanting a child in the future was associated with a higher rate of repeat pregnancy, but contraceptive use at 12 months postpartum was not associated with repeat pregnancies. These results highlight the importance of understanding factors associated with the dissonance between fertility intentions and contraceptive use and childbearing to ensure delivery of quality integrated reproductive health services in the PMTCT framework.